Government Policy Strategy in Countering the Threat of Disintegration: Analysis within the Framework of National Resilience - Bayuna, I Wayan (LPPM Universitas PGRI Sumatera Barat, 2023)
National disintegration is a serious threat that can weaken the stability and sustainability of the Unitary State of the Republic of Indonesia. This phenomenon is reflected in increasing horizontal conflict, political polarization, intolerance, socio-economic disparities, and the spread of disinformation that has the potential to undermine national unity. This study aims to analyze the government's policy strategy in countering the threat of disintegration using the national resilience framework as an analytical tool. The research method used is a descriptive qualitative approach by reviewing policy documents, academic literature, and relevant secondary data. The analysis results show that the government's strategy is realized through several aspects, namely strengthening ideology through the internalization of Pancasila values, inclusive political consolidation, equitable distribution of economic development, preservation of socio-cultural values based on Bhinneka Tunggal Ika, and improvement of the defense and security system, including cybersecurity. However, the implementation of these policies still faces challenges such as limited inter-institutional coordination, low national literacy in some communities, and weak oversight in the implementation of regulations. Therefore, a collaborative strategy based on the Pentahelix model involving the government, academics, the business world, the media, and the community is needed to strengthen national integration. This research confirms that national resilience can only be achieved if the government's policy strategy is accompanied by the active participation of all elements of the nation